A software defined network controller quantitative and qualitative analysis - Bispo, Pedro José Neves (2019)
New challenges are being raised in the networking field with the increasing number of connected devices. The growth of mobile data usage has to be considered as a requirement for the deployment of future 5G networks, especially regarding mobility scenarios. Software-Defined Networking (SDN) enables a greater degree of dynamism and simplification for the deployment of those 5G networks. SDN provides the separation of the control plane from the forwarding plane, allowing more control, adaptability and cost reduction. The growth of SDN integration in new mechanisms and network architectures led to the development of different controller solutions, with a wide variety of characteristics. Several SDN controllers exist, which originated from the different needs of operators and research teams. That resulted in the development of their own controller versions, which made comparison efforts more difficult. As such, this work provides a wider study of several open-source controllers, (namely, OpenDaylight (ODL), Open Network Operative System (ONOS), Ryu and POX), by evaluating not only their performance, but also their characteristics in a qualitative way. Taking performance as a critical issue among SDN controllers, several criteria were evaluated by benchmarking the controllers under different operational conditions, using the Cbench tool. Results are presented regarding both qualitative and quantitative comparisons between those SDN controllers under test.